2012
DOI: 10.4028/www.scientific.net/ast.84.45
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Inspired Active Electrolocation Sensors for Inspection of Tube Systems

Abstract: At night, weakly electric fish Gnathonemus petersii use active electrolocation to scan their environment with self generated electric fields. Nearby objects distort the electric fields and are recognized as electric images on the electroreceptive skin surface of the animal. By analyzing the electric image, G. petersii can sense an object’s distance, dimensions and electrical properties. The principles and algorithms of active electrolocation can be applied to catheter-based sensor systems for analysing wall ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 11 publications
(23 reference statements)
2
8
0
Order By: Relevance
“…The dimensions of the assessed parameters mentioned above for each synthetic plaque are listed in table 1. Note that the atherosclerosis model (artificial blood vessels and plaques) used in this and previous studies [11,14,39] could only to a certain extend mimic the dimensions of a real coronary artery and the complex electrical properties of real arteries and plaques [5,9,10,42,43]. Hence some plaque dimensions such as the overall plaque and core size, were oversized and the complex electrical properties were oversimplified due to using materials that caused mainly resistive effects.…”
Section: Agarose Atherosclerosis Modelmentioning
confidence: 96%
See 4 more Smart Citations
“…The dimensions of the assessed parameters mentioned above for each synthetic plaque are listed in table 1. Note that the atherosclerosis model (artificial blood vessels and plaques) used in this and previous studies [11,14,39] could only to a certain extend mimic the dimensions of a real coronary artery and the complex electrical properties of real arteries and plaques [5,9,10,42,43]. Hence some plaque dimensions such as the overall plaque and core size, were oversized and the complex electrical properties were oversimplified due to using materials that caused mainly resistive effects.…”
Section: Agarose Atherosclerosis Modelmentioning
confidence: 96%
“…Our previous studies [11,14,39] have shown that width and shape of amplitude images depended on the overall size of a synthetic plaque as well as the distance between the sender (S) and the selected receiver (R1 or R3) of the catheter. When the sender-receiver distance was greater than the plaque size (for e.g.…”
Section: Recording and Processing Of Dynamic Electric Imagesmentioning
confidence: 99%
See 3 more Smart Citations